2021
DOI: 10.1002/oby.23309
|View full text |Cite
|
Sign up to set email alerts
|

Combining a β3 adrenergic receptor agonist with alpha‐lipoic acid reduces inflammation in male mice with diet‐induced obesity

Abstract: Objectives Beta‐3 adrenergic receptors (β3‐AR) stimulate lipolysis and thermogenesis in white and brown adipose tissue (WAT and BAT). Obesity increases oxidative stress and inflammation that attenuate AT β3‐AR signaling. The objective of this study was to test the hypothesis that the combination of the β3‐AR agonist CL‐316,243 (CL) and the antioxidant alpha‐lipoic acid (ALA) would lower inflammation in diet‐induced obesity (DIO) and improve β3‐AR function. Methods A total of 40 DIO mice were separated into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…LIPT1 is a vital gene encoding the mitochondrial lipoic acid pathway (9). Abdul et al (18) reported that lipoic acid reduces obesity-induced inflammation in the body by modulating the immune system when chronic treatment with lipoic acid agonists is administered. In addition, the synthesis of mitochondrial fatty is inextricably linked to LIPT1 expression (19).…”
Section: Discussionmentioning
confidence: 99%
“…LIPT1 is a vital gene encoding the mitochondrial lipoic acid pathway (9). Abdul et al (18) reported that lipoic acid reduces obesity-induced inflammation in the body by modulating the immune system when chronic treatment with lipoic acid agonists is administered. In addition, the synthesis of mitochondrial fatty is inextricably linked to LIPT1 expression (19).…”
Section: Discussionmentioning
confidence: 99%
“…Discontinuous treatment of Sprague-Dawley rats with α-lipoic acid at 50 mg/kg body weight prevented gain in body weight and had a protective e cacy on the cardiovascular system by decreasing metabolic and cardiac perturbations (Pop et al, 2020). In another study, chronic treatment of diet induced obese mice with 250 mg/kg of α-lipoic acid in combination with β3-AR agonist CL 316,243 improved body mass composition, reduced body fat percentage by 9% and improved systemic and epididymal white adipose tissue in ammation (Abdul Sater et al, 2022). C57Bl/6J mice fed with a high fat diet and administered with α-lipoic acid at 2.5g/kg of food in conjunction with exercise on treadmill showed improved fatty acid oxidation and reduced visceral adipose tissue (Le Garf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%